Pillars of their practice: an analysis of preservice teachers’ beliefs, where they come from, and how they develop - Burke, Katherine J.; Walls, Maria Aguilar; Fukawa-Connelly, Timothy; Smith, Michael; Crass, Casey; Kelley, Sue; Wagner, Elvis (Frontiers in Education, 2025)
Drawing on a series of interviews of teacher residents, this study investigates residents’ foundational beliefs, the influences that shaped them, and the extent to which they changed during their residencies. This study has three primary findings. First, residents developed a more sophisticated understanding of what relational teaching entails. Second, residents increasingly recognized the importance of making real-world connections as a motivator, though they did not fully recognize the extent to which students’ individual or cultural knowledge could be as an instructional resource. Third, residents increasingly asserted their teacherly identities and used their university courses as tools for reflection, rather than as dictates to be followed.